Evidence for photo-induced charge separation between dye molecules adsorbed to aluminium oxide surfaces - Cappel,UB; Moia,D; Bruno,A; Vaissier,V; Haque,SA; Barnes,PRF (Scientific Reports, 2016)
Excited state dynamics and photo-induced charge transfer of dye molecules have been widely studied due to their relevance for organic and dye-sensitised solar cells. Herein, we present a femtosecond transient absorption spectroscopy study of the indolene dye D131 when adsorbed to inert Al2O3 substrates for different surface concentration of the dye. Surprisingly, we find that at high surface concentrations, the first singlet excited state of the dye is converted into a new state with an efficiency of about 80%. We assign the absorption features of this state to the oxidised dye and discuss the possibility of photo-induced charge separation between neighboring dye molecules. Our study is the first to show that this process can be highly efficient without the use of donor and acceptor molecules of different chemical structures.